The impact of public debt on financial stability in Iraq - كاظم اسراء صادق; علوان غفران حاتم (Journal of Economics and Administrative Sciences, 2020)
Countries have faced the challenges of high levels of public debt and seek to define the optimum limits to reduce risks to which the financial system can be exposed and its impact on the economy as a whole. Hence the importance of research in studying the impact of internal and external public debt components on indicators of stability of the financial system for the period 2005-2017 for the purpose of knowing the extent of the financial stability indicators response to the high level of the public debt from its optimum ratio, as the aim of the research is to estimate and analyze the dynamic relationship of short and long term between the components of public debt and indicators of financial stability using the (ARDL) model that requires the time-series of the dependent variable to remain At the first difference, as the estimate results showed that the foreign reserve as a macroeconomic indicator was affected by the rise in internal debt, especially for the years (2014-2017), after the government went to the sources of internal debt to finance the budget deficit, as the contribution of the domestic debt to the GDP reached 49% in 2017 in addition to The contribution of non-bank financial institutions to the internal lending process after it was controlled by banks until the year 2010. The research found that the total banking capital (index of the banking sector) was adversely affected by the internal and external debt in the short term and their influence on it in the long term has weakened due to the high capital adequacy attributable to the modest employment of banks resources, and the results of the estimate reached the impact of the volume of stock trading (the financial market index) Inversely to the increase in domestic debt in the short and long term due to the decrease in the number of registered shares and the failure of disclosure reports.